2022
DOI: 10.1177/01492063211063807
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity or Self-Enhancement? Effects of Self-Presentation and Authentic Leadership on Trust and Performance

Abstract: We theorized and tested an integrated model that examines the simultaneous effects of authentic self-expression and self-enhancement (including authentic and exaggerated self enhancement) on employee outcomes. Using a multisource, two-wave survey design and a sample of 143 working groups from 566 employees, we tested the indirect effects of self-presentation on job performance through (a) trust from coworkers and (b) felt trust from coworkers. We found that through trust from coworkers, authentic self-expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 85 publications
3
14
1
2
Order By: Relevance
“…Example items include “My quantity of work is higher than average” and “My efficiency is much higher than average.” It was rated on a 5-point Likert-type scale, ranging from 1 ( strongly disagree ) to 5 ( strongly agree ). The reliability and validity of this scale were confirmed by previous studies in both Chinese and Western culture (Kim et al, 2022b; Yu et al, 2021). Moreover, engaging unethical behaviors towards leaders or counterproductive work behaviors were negatively associated with task performance (Dalal et al, 2009; Mackey et al, 2021).…”
Section: Methodssupporting
confidence: 79%
“…Example items include “My quantity of work is higher than average” and “My efficiency is much higher than average.” It was rated on a 5-point Likert-type scale, ranging from 1 ( strongly disagree ) to 5 ( strongly agree ). The reliability and validity of this scale were confirmed by previous studies in both Chinese and Western culture (Kim et al, 2022b; Yu et al, 2021). Moreover, engaging unethical behaviors towards leaders or counterproductive work behaviors were negatively associated with task performance (Dalal et al, 2009; Mackey et al, 2021).…”
Section: Methodssupporting
confidence: 79%
“…Their results indicated that AL exhibited by leaders can evoke OT from followers. Other researchers came to similar conclusions: Swain, Cao, and Gardner (2018); Khalil and Siddiqui (2019); and Kim, David, Chen, and Liang (2022). From the above literature review, it was hypothesized that: H2: AL is positively related to OT.…”
Section: Authentic Leadership and Organizational Trustmentioning
confidence: 59%
“…Shinde's (2018) study results revealed a significant correlation between authentic leadership of the leaders and subordinates' well-being in the Petroleum industry. Similarly, Kim et al (2022) in their study affirm that authentic self-enhancement had a positive indirect effect on job performance, whereas exaggerated self-enhancement had a negative indirect effect. In the same vein, Sainz et al (2021) found that higher authentic leadership predicted lower organizational dehumanization and stress at work.…”
Section: Authentic Leadership and Physical Asset Management Practicesmentioning
confidence: 59%